A STUDY ON THE NON-ASSOCIATIVE RINGS AND DEVELOPMENTS - Tiwari, Deepak; kushwah, Dr Jaya (Innovative Research Thoughts, 2021)
With the help of this paper, we want to show a broad survey and growth of current review of non-associative rings and compute some of their different types of application in various ways till date. All these applications describe and exhibit the ample work in various fields of non-associative rings and by which different algebraic framework in theoretical overview could be grown.